A Review on the Performance of Organic Rankine Cycle with Different Heat Sources and Absorption Chillers. Issue 2 (1st March 2018) - Pathak, Saurabh; Shukla, S.K.
ABSTRACT: This article reviews the performance of organic Rankine cycle with different heat sources. Plenty of waste heat is widely available in low to medium temperature range from various sources such as engines, machines and processes. The conversion of these low-grade waste heat into electricity is a feasible solution to provide clean energy. The Organic Rankine Cycle (ORC) is a suitable thermal cycle for the waste heat recovery application. The thermodynamic performance of ORC with different operational parameters and several working fluids is discussed. Further, the feasibility of integration of various absorption chillers in ORC, which is run by low-grade waste heat available at the outlet of the evaporator of ORC is evaluated.